Personality traits as determinants of mindfulness in FISM World Champions of Magic - Napora, Wojciech; Julia, Guilhem (Przegląd Psychologiczny, 2021)
Aim The study aimed to check how the Big Five personality traits relate to the level of mindfulness in the FISM World Champions of Magic. Method Participants were champions of magic (N = 50) from 20 countries. International Personality Item Pool Big Five Markers 50 (IPIP-BFM-50) and Mindful Attention Awareness Scale (MAAS) were used to measure personality traits and mindfulness, respectively. Results Regression analysis showed that emotional stability and conscientiousness explained 47% of mindfulness in champions of magic. Conclusion Only two personality traits predicted mindfulness in magicians, which should be interpreted as a preliminary result.